The Principles and Practices of Akad Ijarah: A Research Application in Islamic Banking - Eka Darwanti; Suci Diah Sririzki; Rahmandani Nor Ramadhan; Zaitun Qamariah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This article investigates the principles and practices of Akad Ijarah and its application in Islamic banking. Using a literature review method, this article explores the fundamental concept of Akad Ijarah and analyzes its implementation in the context of Islamic banking. The research aims to provide a deep understanding of the structure, mechanisms, and benefits of Akad Ijarah for Islamic financial institutions. The analysis results present a comprehensive overview of how Akad Ijarah is implemented in the practices of Islamic banking, as well as the challenges and opportunities it faces. These findings have significant implications for the development of Islamic banking products and services that adhere to Shariah principles. In conclusion, this research highlights the importance of a solid understanding of Akad Ijarah in ensuring the compliance of Islamic banking with Shariah principles.